Inflation Dynamics and Monetary Policy Transmission in Vietnam and Emerging Asia - Bhattacharya, Rina. (Washington, D.C. : International Monetary Fund, 2013)
This paper provides an overview of inflation developments in Vietnam in the years following the doi moi reforms, and uses empirical analysis to answer two key questions: (i) what are the key drivers of inflation in Vietnam, and what role does monetary policy play? and (ii) why has inflation in Vietnam been persistently higher than in most other emerging market economies in the region? It focuses on understanding the monetary policy transmission mechanism in Vietnam, and in understanding the extent to which monetary policy can explain why inflation in Vietnam has been higher than in other Asian emerging markets over the past decade.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet